ANC in new normal adaptation era: Challenge and opportunity - Inge Ayu Wardani Sakinah (BKM Public Health and Community Medicine, 2021)
Objective: This paper aims to describe challenges and opportunities in implementing various ANC models in the new normal adaptation era based on a literature review. Content: COVID-19 pandemic not only increased morbidity and mortality but also affect various sectors, including the health care system in Indonesia. ANC is one of those affected indicated by decreased coverage of K1 and K4. Restrictions on maternal and newborn health services, recommendations to delay ANC visits, feeling worried about getting infected by COVID-19, are several reasons why mothers decide not to do ANC visits. The barrier to access optimal health services may cause health problems. Other countries overcome this by using various models to deliver ANC, such as telehealth, home visits, hybrid model, and scheduled appointment. In developed countries, telehealth offered several classes to improve maternal and fetus health, and mHealth for mental consultations. Home visits are also carried out by considering mother condition and risk management for both mothers and health workers. Hybrid Models which combine telehealth and in-person visits are important for high-risk pregnancy with some considerations such as USG examination, a complete diagnostic examination in early pregnancy, and complications management. Another model has scheduled appointments based on the time agreement by mother and health workers with the standards for preventing COVID-19 transmission, shortening meeting duration, and arranging consultation schedules to avoid queues. In Indonesia, adopting only one model seems not feasible, but a combination of several models can be applied as an alternative. Home visits and schedule appointments have been implemented, but standard general guideline prevention of transmission and standard services must be made properly. Telehealth and Tele counseling can be used for routine visits, but they can’t guarantee the quality of ANC. More consideration is K1 must be done directly followed by the scheduled appointment model, while telehealth and Tele counseling can be complemented. Conclusion: The ANC service system in the new normal era must combine several models to ensure the quality and quantity of ANC visits.